Experimental Study of the Effect of Air Input on Temperature Distribution Inside a Tropical Greenhouse Using Natural Convection - Muhammad Razis; Abdul Gafur; Murdani (International Journal of Science and Environment (IJSE), 2026)
This study employed an experimental research method with a quantitative approach to investigate the effect of air inlet position and opening area on temperature distribution inside a tropical greenhouse utilizing natural convection. Three ventilation configurations were tested: V1 with a bottom air inlet and an opening area of 0.02 m², V2 with a middle air inlet and an opening area of 0.04 m², and V3 with a top air inlet and an opening area of 0.06 m². The experiment was conducted in a naturally ventilated tropical greenhouse under controlled conditions while maintaining constant greenhouse dimensions, covering materials, measurement schedules, and weather conditions. Environmental parameters, including air temperature, relative humidity, and air velocity, were measured at twelve observation points distributed throughout the greenhouse using thermocouples, a hygrometer, and an anemometer. Data collection was carried out during the morning, midday, and afternoon to evaluate the daily variation of the greenhouse microclimate. The collected data were analyzed based on the principles of heat transfer, including conduction, natural convection, and thermal radiation, to determine the influence of different ventilation configurations on airflow circulation and thermal performance. The experimental method enabled direct observation of the relationship between air inlet configuration and the resulting environmental conditions, providing a reliable basis for evaluating the effectiveness of natural ventilation in improving temperature distribution and overall microclimate quality inside tropical greenhouses.